Clinico-epidemiological Study on Self-induced Poisoning Caused by Substances Other than Organophosphorus Compound - Ara, Ismat; Erfan Uddin, Rabiul Alam Md; Ghose, Aniruddha (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Though Organophosphorus Compounds (OPC) are mostly used for self-induced poisoning, non- OPC poisoning cases are increasing day by day. This study was done to describe clinical pattern and outcome of poisoning other than OPC. Materials and methods: This observational study was conducted in the Medicine Ward of Chittagong Medical College Hospital. Data were collected in structured case record forms. Total 204 patients (n=204) were included in the study after fulfilling the inclusion criteria. Data were analyzed with SPSS and expressed as percentage, mean with standard deviation as appropriate. Results: Out of 204 patients, most were female (60.8%). Most of the patients were young, 56.9% patients were unmarried, 60.8% poisoned patients resided in metropolitan area, most were with low educational level, 57.4% patients came from the middle class socioeconomic group, 82.4% patients were poisoned by a single agent and 17.6% by multiple agents. Offending agents were identified in 96.6% cases. Poisoning by drugs was the highest (47.1%) followed by rat killer poisoning (22.5%) poisoning by non-OPC insecticides (6.9%) corrosive poisoning (6.4%) chemical poisoning (3.9%) and alcohol poisoning (1%). Family disharmony was the underlying cause of self-harm in 47.1% cases, financial constraints in 8.3%, social crisis in 7.8%, failure in love affairs in 6.4% and academic failure in 2.5% patients. 14.7% patients poisoned themselves to gain some benefit by the act of self-harm. 81.4% patients were discharged with advice, 2.9% died. Conclusion: Burden of Non-OPC poisoning is high. Outcome is not so fatal as OPC, but the problem has to be addressed in large scale. JCMCTA 2021 ; 32 (2) : 34-40